2017
DOI: 10.1001/jamadermatol.2017.2105
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Nonblanching, Palpable Skin Lesions With a Linear Pattern in Children With Henoch-Schönlein Syndrome

Abstract: inear nonblanching skin lesions sometimes develop in apparently healthy skin following mechanical friction. This tendency, often termed Köbnerization, is common in psoriasis, lichen planus, vitiligo, and many bullous dermatoses. 1 Very rarely, such lesions have also been documented in patients with Henoch-Schönlein syndrome, an immunoglobulin A-dominant leukocytoclastic small vessel vasculitis. [2][3][4][5][6][7][8] This report presents our prospective experience with linear nonblanching skin lesions in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, on day 32 after the first onset of abdominal pain, purpura appeared on the extensor surfaces of lower extremities (Figure 2(a)). No other cutaneous lesions, such as linear nonblanching lesion or bullous lesion, 11,12 were observed. Thus, nonthrombocytopenic purpura in lower extremities, together with recurrent abdominal pain, indicated the diagnosis of HSP.…”
Section: Case Reportmentioning
confidence: 87%
“…However, on day 32 after the first onset of abdominal pain, purpura appeared on the extensor surfaces of lower extremities (Figure 2(a)). No other cutaneous lesions, such as linear nonblanching lesion or bullous lesion, 11,12 were observed. Thus, nonthrombocytopenic purpura in lower extremities, together with recurrent abdominal pain, indicated the diagnosis of HSP.…”
Section: Case Reportmentioning
confidence: 87%
“…The Köbner sign occurs in approximately 10% of patients with a skin-limited or skin-predominant vasculitis [ 4 ]. Furthermore, this sign has been recently identified in approximately every fourth child with Henoch–Schönlein purpura, the most common childhood vasculitis [ 90 ]. Controversy exists as to whether hemorrhagic edema of young children represents the infantile variant of Henoch–Schönlein purpura or whether it is a similar but distinct entity.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that 10% of patients with LCV presented with KP (n = 98), 14 while the other found that 26% of children hospitalized with HSP presented with KP (n = 31). 15 Interestingly, there have also been two case reports on the topic of reverse KP in LCV, in which skin lesions have disappeared at the sites of trauma. 5,16…”
Section: Discussionmentioning
confidence: 99%